If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2 + -1x) = -15 (2 * -3 + -1x * -3) = -15 (-6 + 3x) = -15 Solving -6 + 3x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = -15 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = -15 + 6 3x = -15 + 6 Combine like terms: -15 + 6 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| F(x)=x^4-8x^3+18x^2+6 | | 3x-7x+5=3-5x | | 18x-28=x+380 | | 6+0.1x=0.15x+18 | | 10x+24=64 | | x+34+x+34=6x-28 | | 8(2x+1/4)=5(3-4x) | | 2(3m-6+3m)=2m | | 6a-9=6+a | | -5p+49=14 | | 5(k-2)=(3k+9) | | x-38+x+98=180 | | 3x-6+6=21+6 | | 7n-19=65 | | 28=x | | k^3-15k^2+5k=0 | | x+1+x-7=90 | | z=8-14i | | V(x)=x(12-2x) | | s=4n^2r^2 | | 8x+67y=5000 | | 19+6b=79 | | 40-r=24 | | 3ax^2=4bx+12 | | h+4.7=10.2 | | 4x+13=22 | | 52-u=10 | | v+v= | | 4=2y+12 | | 74-v=47 | | w^2=3(w+-1) | | c+23=26 |